2013
DOI: 10.5539/ibr.v6n7p131
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal Policy and Growth: An Empirical Evaluation in CFA Franc Zone

Abstract: This paper evaluates the link between fiscal policy and growth. For this purpose, we evaluate the influence of the level of public expenditures and revenues as well as the composition of the budget on economic growth. Relying on data provided by African Development Indicators, our sample is made of 9 countries of the CFA Franc Zone over the period 1990-2010. Focusing on panel data techniques, our analysis leads to the following results: (i) public expenditures reduce significantly growth; (ii) an increase in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Meanwhile, Ndjokou (2013) assessed the link between fiscal policy and growth. To this end, the author investigated the influence of the composition of the budget on economic growth in nine countries of the CFA Franc zone over the period of 1990-2010.…”
Section: Empirical Evidence and Research Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, Ndjokou (2013) assessed the link between fiscal policy and growth. To this end, the author investigated the influence of the composition of the budget on economic growth in nine countries of the CFA Franc zone over the period of 1990-2010.…”
Section: Empirical Evidence and Research Methodologymentioning
confidence: 99%
“…The analysis of previous studies revealed that there is a lack of research in government spending nexus economic growth in the EU-28 countries. Most of the studies focused either on specific, mostly developing country (Tang, 2009; Hamzah, 2011; Loto, 2011; Taiwo and Abayomi, 2011; Zamanian et al , 2012; Chude and Chude, 2013; Ndjokou, 2013; Gisore et al , 2014; Olulu et al , 2014), or performed analysis on large-scale covering at least 30 developed and developing countries (Wu et al , 2010). Meanwhile, the other researchers, even concentrating on the EU problems, more investigated government debt impact on economic growth (Drisaki, 2013; Spilioti and Vamvoukas, 2015) or EU budget allocation problems, rather than paid attention on government spending and economic growth.…”
Section: Empirical Evidence and Research Methodologymentioning
confidence: 99%
“…Ndjokou [25] examined the interaction between fiscal policy and economic growth in nine West Africa CFA franc Zone countries using panel data. Specifically, the study sought to analyze the influence of public expenditures and revenues in addition to the budget composition of these economies on growth.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…When a budget shortfall occurs, broad arrays of strategies and policies are considered to fight budget deficits (Ndjokou, 2013). An examination of these strategies within the context of the oil crisis of 2014 provides pivotal information for the reader and the literature.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Second, revenue-increasing strategies aim to grow the economy by implementing policies that enhance budget revenues without severely affecting public spending or creating market hostility (Ndjokou, 2013;Garcia & Hé nin, 1999). Implementing revenue-increasing strategies during economic recessions can be extremely challenging.…”
Section: Literature Reviewmentioning
confidence: 99%